Collective liability in Islam : the 'āqila and blood-money payments / Nurit Tsafrir. - Tsafrir, Nurit, 1957- (Cambridge studies in Islamic civilization., 2020)
Offering the first close study of the Aqila, a group collectively liable for blood money payments on behalf of a member who committed an accidental homicide, Nurit Tsafrir analyses the group's transformation from a pre-Islamic custom to an institution of the Shari'a, and its further evolution through medieval and post medieval Islamic law and society. Having been an essential factor in the maintenance of social order within Muslim societies, the Aqila is the intersection between legal theory and practice, between Islamic law and religion, and between Islamic law and the state. Tracing the history of the Aqila, this study reveals how religious values, state considerations and social organization have participated in shaping and reshaping this central institution, which still concerns contemporary Muslim scholars.